Hemicrania Continua Headache in a Veteran with Posttraumatic Stress Disorder and Major Depressive Disorder without Traumatic Brain Injury - Brandon A. Kohrt; Erica Duncan (Case Reports in Psychiatry)
Hemicrania continua is a headache characterized by chronic unremitting unilateral pain associated with ipsilateral autonomic findings. This type of headache responds to high-flow oxygen and indomethacin. This case report describes a male veteran with posttraumatic stress disorder (PTSD) and major depressive disorder who suffers from comorbid hemicrania continua. The psychiatric symptoms were recalcitrant to psychopharmacological intervention. However, when the patient's hemicrania continua was treated appropriately, the patient's psychiatric symptoms also abated. This case demonstrates the need to address physical comorbidities that may exacerbate psychiatric disorders, such as PTSD.